PENERAPAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN BUMN PADA PT JASA MARGA PERSERO TBK: Implementation of Social and Environmental Responsibility of BUMN at PT Jasa Marga Persero Tbk - Ananda, Salsabila Putri; Yunari, Sri Bakti (AMICUS CURIAE, 2024)
BUMN (State-owned enterprises) are obligated to implement social and environmental responsibilities (TJSL BUMN), including PT. Jasa Marga Persero Tbk. Where PT. Jasa Marga Persero Tbk's TJSL prioritizes education, environment, and SMEs. How is the implementation of Social and Environmental Responsibility of State-Owned Enterprise PT Jasa Marga and What are the obstacles in the implementation of Social and Environmental Responsibility at PT Jasa Marga? The research method used is normative legal type, utilizing secondary data and analyzed qualitatively to draw deductive conclusions Based on the analysis of the implementation of TJSL BUMN at PT. Jasa Marga Persero Tbk has been running effectively but not yet optimal because there are several problems related to TJSL BUMN for SME development programs and social services. The obstacles faced include external and internal obstacles.